Congenital Anomalies Programmed by Maternal Diabetes and Obesity on Offspring of Rats - Araujo-Silva, Vanessa Caruline; Santos-Silva, Alice; Lourenço, Andressa Silva; Barros-Barbosa, Cristielly Maria; Moraes-Souza, Rafaianne Queiroz; Soares, Thaigra Sousa; Karki, Barshana; Paula, Verônyca Gonçalves; Sinzato, Yuri Karen; Damasceno, Débora Cristina; Volpato, Gustavo Tadeu (Frontiers in Physiology, 2021)
Embryo-fetal exposure to maternal disorders during intrauterine life programs long-term consequences for the health and illness of offspring. In this study, we evaluated whether mild diabetic rats that given high-fat/high-sugar (HF/HS) diet presented maternal and fetal changes at term pregnancy. Female rats received citrate buffer (non-diabetic-ND) or streptozotocin (diabetic-D) after birth. According to the oral glucose tolerance test (OGTT), the experimental groups (n=11 animals/group) were composed of: Non-diabetic and Diabetic receiving standard diet (S) or HF/HS diet. High-fat/high-sugar diet (30% kcal of lard) in chow and water containing 5% sucrose and given one month before mating and during pregnancy. During and at the end of pregnancy, obesity and diabetes biomarkers were determined. After laparotomy, blood samples, periovarian fat and uterine content were collected. The diabetic rats presented a higher glycemia and percentage of embryonic losses when compared to NDS group. Rats DHF/HS presented increased obesogenic index, caloric intake and periovarian fat weight and reduced gravid uterus weight in relation to the other groups. Besides, this association might lead to inflammatory process, confirmed by leukocytosis. Obese rats (NDHF/HS and DHF/HS) showed higher triglyceride levels and their offspring with lower fetal weight and ossification sites, indicating intrauterine growth restriction. This finding may contribute to vascular alterations related to long-term hypertensive disorders in adult offspring. The fetuses from diabetic dams showed higher percentages of skeletal abnormalities, and DHF/HS dams still had higher rate of anomalous fetuses. Thus, maternal diabetes and/or obesity induces maternal metabolic disorders contribute to affect fetal development and growth.